„Na Antenie” i „Wiadomości”: okoliczności rozpoczęcia i zakończenia współpracy - Moczkodan, Rafał (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2017)
NA ANTENIE AND WIADOMOŚCI: THE CIRCUMSTANCES OF THE BEGINNINGS AND TERMINATION OF COOPERATION The article discusses the origins of the cooperation between Jan Nowak-Jeziorański from Radio Free Europe and Mieczysław Grydzewski, editor of London’s weekly Wiadomości. It resulted in the establishment of the magazine Na Antenie, which was a supplement to the Wiadomości in the years 1963–1969. The second part of the article discusses the circumstances putting an end to their cooperation, highlighting the role played by a polemic by Józef Mackiewicz published in the London weekly.